2008
DOI: 10.1007/s00192-008-0563-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up after vaginal sacrospinous fixation: patient satisfaction, anatomical results and quality of life

Abstract: The objective of this study is to evaluate long-term anatomical results, symptoms of descent, and quality of life after vaginal sacrospinous fixation (SSF) through postoperative follow up study from one institution. Ninety nine women (mean 66 years) underwent vaginal SSF for vault prolapse at our institution. We contacted all patients 2-15 years after surgery for examination (POP-Q, survey). Sixteen out of 55 (29%) patients, who completed follow-up, presented with cystocele, three patients with rectocele, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 16 publications
2
29
1
1
Order By: Relevance
“…The objective cure rate at median follow‐up of 86 months for all patients ( n = 146) for overall compartments in this study was 67.8%, with the anterior compartment being the commonest site of recurrence, accounting for 29.4%. The present findings are similar to that of a previous study by Aigmueller et al ., who reported an objective success rate of 64% with 29% anterior compartment recurrence, with a median follow‐up of 7 years . Hefni and El‐Toukhy reported a much higher success rate, 96% at mean follow‐up of 57 months, but successful outcome was based on recurrence at the apical compartment rather than overall compartments .…”
Section: Discussionmentioning
confidence: 99%
“…The objective cure rate at median follow‐up of 86 months for all patients ( n = 146) for overall compartments in this study was 67.8%, with the anterior compartment being the commonest site of recurrence, accounting for 29.4%. The present findings are similar to that of a previous study by Aigmueller et al ., who reported an objective success rate of 64% with 29% anterior compartment recurrence, with a median follow‐up of 7 years . Hefni and El‐Toukhy reported a much higher success rate, 96% at mean follow‐up of 57 months, but successful outcome was based on recurrence at the apical compartment rather than overall compartments .…”
Section: Discussionmentioning
confidence: 99%
“…The level of postoperative vaginal support chosen as a criterion for operative failure has been discussed in the urogynecologic literature (13). Several studies have demonstrated that strict anatomic definitions result in lower reported success rates than the use of subjective satisfaction (5, 8, 14-15). Our findings demonstrate that prolapse below the hymen indeed affects patient satisfaction, whereas women with vaginal walls at the hymen are equally satisfied as those with higher vaginal walls.…”
Section: Discussionmentioning
confidence: 99%
“…However, dyspareunia can pose an important problem after vaginal surgery. The studies have reported a de novo dyspareunia rate of 3.2% after SSF (24). In a study by Hefni et al (25), only two patients (1%) had de novo dyspareunia because of vaginal stenosis that developed in relation to perineorrhaphy.…”
Section: Discussionmentioning
confidence: 98%